Temporal profiles of systolic blood pressure variability and neurologic outcomes after endovascular thrombectomy. (December 2022) - Prasad, Ayush; Kobsa, Jessica; Kodali, Sreeja; Bartolome, David; Begunova, Liza; Quispe-Orozco, Darko; Farooqui, Mudassir; Zevallos, Cynthia; Ortega-Gutiérrez, Santiago; Anadani, Mohammad; Almallouhi, Eyad; Spiotta, Alejandro M; et al.
Introduction: Observational studies have found an increased risk of hemorrhagic transformation and worse functional outcomes in patients with higher systolic blood pressure variability (BPV). However, the time-varying behavior of BPV after endovascular thrombectomy (EVT) and its effects on functional outcome have not been well characterized. Patients and methods: We analyzed data from an international cohort of patients with large-vessel occlusion stroke who underwent EVT at 11 centers across North America, Europe, and Asia. Repeated time-stamped blood pressure data were recorded for the first 72 h after thrombectomy. Parameters of BPV were calculated in 12-h epochs using five established methodologies. Systolic BPV trajectories were generated using group-based trajectory modeling, which separates heterogeneous longitudinal data into groups with similar patterns. Results: Of the 2041 patients (age 69 ± 14, 51.4% male, NIHSS 15 ± 7, mean number of BP measurements 50 ± 28) included in our analysis, 1293 (63.4%) had a poor 90-day outcome (mRS ⩾ 3) or a poor discharge outcome (mRS ⩾ 3). We identified three distinct SBP trajectories: low (25%), moderate (64%), and high (11%). Compared to patients with low BPV, those in the highest trajectory group had a significantly greater risk of a poor functional outcome after adjusting for relevant confounders (OR 2.2; 95% CI 1.2–3.9; p = 0.008). In addition, patients with poor outcomes had significantly higher systolic BPV during the epochs that define the first 24 h after EVT ( p < 0.001). Discussion and conclusions: Acute ischemic stroke patients demonstrate three unique systolic BPV trajectories that differ in their association with functional outcome. Further research is needed to rapidly identify individuals with high-risk BPV trajectories and to develop treatment strategies for targeting high BPV.